Implikasi Bimbingan Kelompok Terhadap Penyesuaian Diri Siswa di Madrasah Aliyah - Noraida Azizah; Ihsan Mz; Gerry Olvina Faz (Institut Agama Islam Negeri Curup, 2023)
This study is intended to help students adapt themselves and see the extent of the group guidance implications for the student's adaptation. Self-adjustment is needed especially for students who enter a new school, where self-adjustment is an individual's ability to meet the demands, both within himself and in the ward. The study used a descriptive qualitative approach to be able to see the process through an analyst for phenomena that occur in the field on factual issues and look at the comprehensive implications, with the subject of two male students and three female students. As a result of this study indicates improvement, students who follow group guidance convey aspirations and messages to be addressed by educators. In the performance of a group of student guides feeling its therapeutic effect, students can learn to appreciate, listen and speak with confidence.